QUALPRO-RP - An Errors Management and Rework Effort Measurement Tool - Lee, Yun Kiew; Hj. Yaacob, Mashkuri; Ow, Siew Hock (Malaysian Journal of Computer Science, 2002)
Periodic reviews of different events and milestones during the software development phases are vital, both to management visibility and progress of the development. There are both formal and informal reviews. Various errors will surface during the review process. A tool is needed to manage the errors and rework systematically. This paper highlights on the development of a Computer-Aided Software Engineering (CASE) tool for errors management and rework effort measurement in Software Quality Assurance (SQA).